Developing Educational Materials for Smartphone Photography Instruction - Thanankorn Premrattanachai; Kittichai Kasemsarn (The International Journal of Visual Design, 2026)
The study aims to develop and validate evidence-based design principles for educational materials in interactive smartphone photography that meet the learning and accessibility needs of older adults. The study utilized a mixed-methods design that involved expert consultation, user needs assessment (interviews), prototype development, and validation testing (questionnaires). The structured interviews included two graphic and two photography educators. This was followed by in-depth interviews with ten seniors aged between 60 and 70. These interviews examined their learning preferences and their interaction with technology. Grounded in the findings, the researchers created a prototype of fifty-three interactive book pages on travel, portrait, and food photography. Validation was conducted through a structured three-hour workshop with ten seniors, using a set of satisfaction assessment tools. Results demonstrated consistently high satisfaction ratings across multiple assessment dimensions. Typography and other visual design elements attained the highest scores (M = 4.9, SD = 0.32). Participants strongly preferred self-paced study and easily approachable instructor guidance. Research also validated the previously established design specifications, including 18- to 20-point type, sufficient visual contrast, and other layout simplifications, as vital accessibility components. This study formulated empirically validated design specifications for the education of older adults in smartphone photography, while also illustrating the design and deployment of age-inclusive educational practices.
Keywords: Technology Use by Older Adults; Subtitles and Audiovisual Media; Digital Accessibility for Disabilities